Multisystemic BCGitis: A rare complication of intravesical BCG immunotherapy for bladder cancer - Ana T. Vilares, MD; Cláudio Nunes Silva, MD; Miguel Correia da Silva, MD; Joel Sousa, MD; Bárbara Viamonte, MD; António J. Madureira, MD (Radiology Case Reports, 2022)
ABSTRACT: Intermediate- to high-grade non-muscle invasive bladder cancer is preferably treated with transurethral resection followed by adjuvant intravesical immunotherapy with Bacillus Calmette-Guérin (BCG). BCG acts as an immune stimulator, inducing a complex inflammatory response that selectively targets tumoral cells. Mild side effects of BCG instillation, such as fever, malaise, and bladder irritation are frequent, while severe treatment-associated complications of the genito-urinary tract are rare. “Distant” complications are even rarer and, since BCG is able to disseminate hematogenously, virtually all organs and systems can be involved, with the lungs, liver and musculoskeletal system being most commonly affected. Vascular complications of BCG immunotherapy are exceedingly rare and difficult to diagnose, because they can mimic other vascular infections and may occur several years after treatment. Knowledge of previous BCG immunotherapy and awareness about treatment-related complications is essential to avoid misdiagnosis, and to guide appropriate treatment.